2018
DOI: 10.1111/avj.12679
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of Equivac® HeV Hendra virus vaccination on Thoroughbred racing performance

Abstract: No evidence of an effect of Hendra virus vaccination on racing performance was found. The findings allow owners, trainers, industry regulators and animal health authorities to make informed decisions about vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Our study has significant implications for those advocating landscape management to mitigate the risks of HeV spillover. Informed citizens in areas affected by HeV risks support the current emphasis on raising rates of equine HeV vaccination [17, 21]. Moves towards adoption of ecological approaches could find broad social support, but public polarisation around mechanisms for policy implementation points to the need to work with affected communities to co-develop fair, effective and locally appropriate solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has significant implications for those advocating landscape management to mitigate the risks of HeV spillover. Informed citizens in areas affected by HeV risks support the current emphasis on raising rates of equine HeV vaccination [17, 21]. Moves towards adoption of ecological approaches could find broad social support, but public polarisation around mechanisms for policy implementation points to the need to work with affected communities to co-develop fair, effective and locally appropriate solutions.…”
Section: Discussionmentioning
confidence: 99%
“…However vaccine uptake remains suboptimal—even in areas deemed to be at higher risk of HeV spillovers [18]. Factors driving resistance to use of the vaccine include horse owners’ concerns about vaccine cost, safety and its potential impact on equine performance [1921]. The adoption of safer horse-husbandry practices has also been less than ideal.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by the University of Sydney has confirmed that vaccination against the deadly Hendra virus does not affect the performance of racing horses …”
Section: Equinementioning
confidence: 99%
“…For example, widely held views that HeV vaccination compromised athletic performance were investigated in a study of the race‐day performance of 755 horses over 4208 starts before and after HeV vaccination. There was no evidence that HeV vaccine had any effect on the racing performance 19 . Whether published scientific data can drive decision‐making more than social media influencers remains to be seen.…”
mentioning
confidence: 97%